2018
DOI: 10.1002/rth2.12104
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐21 role in aspirin‐dependent PPARα and multidrug resistance protein 4 upregulation

Abstract: BackgroundA mechanism involved in high on‐aspirin treatment residual platelet reactivity is platelet multidrug resistance protein 4 (MRP4) overexpression. Aspirin enhances platelet MRP4 expression with a PPARα‐dependent mechanism and reduces miR‐21 expression that, in turn, downregulates PPARα expression.ObjectiveThe aim of our study was to verify the relationship between miR‐21 and MRP4‐PPARα levels induced by aspirin treatment.MethodsWe evaluated the changes in MRP4‐PPARα, mRNA, MRP4 protein, and miR‐21 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…These data are in line withAn et al (2018) who observed a significant decrease in IL-1β mRNA levels by clopidogrel treatment.Likewise,clopidogrel significantly decreased the hepatic expressions of TIMP1 and TGF-β1, compared toαnaphthylisothiocyanate (xenobiotic)-exposed protease activated receptor-4 in mice treated with vehicle (Joshi et al, 2016). Regarding PPARα, rarelydata linking PPARα with clopidogrel, but contrarily to the present study, Massimi et al (2018) showed that, cells treated with Aspirin, an anti-platelet drug, had up-regulated PPARα mRNA. Anti-platelet treatment by clopidogrel in NALFD ameliorated the hepatic inflammation (Sitia et al, 2013) and abolished vascular inflammatory responses and remodeling (An et al, 2018), as platelet granules contain a variety of factors including TGFβ that are secreted upon platelet activation (Denslow et al, 2017),and a linear correlation of plasma TIMP1 levels and platelet count has been observed by the lower circulating TIMP1 levels in patients on clopidogrel treatment (Nagy et al, 2016).…”
Section: Discussionsupporting
confidence: 48%
“…These data are in line withAn et al (2018) who observed a significant decrease in IL-1β mRNA levels by clopidogrel treatment.Likewise,clopidogrel significantly decreased the hepatic expressions of TIMP1 and TGF-β1, compared toαnaphthylisothiocyanate (xenobiotic)-exposed protease activated receptor-4 in mice treated with vehicle (Joshi et al, 2016). Regarding PPARα, rarelydata linking PPARα with clopidogrel, but contrarily to the present study, Massimi et al (2018) showed that, cells treated with Aspirin, an anti-platelet drug, had up-regulated PPARα mRNA. Anti-platelet treatment by clopidogrel in NALFD ameliorated the hepatic inflammation (Sitia et al, 2013) and abolished vascular inflammatory responses and remodeling (An et al, 2018), as platelet granules contain a variety of factors including TGFβ that are secreted upon platelet activation (Denslow et al, 2017),and a linear correlation of plasma TIMP1 levels and platelet count has been observed by the lower circulating TIMP1 levels in patients on clopidogrel treatment (Nagy et al, 2016).…”
Section: Discussionsupporting
confidence: 48%
“…[2][3][4][5][6] Studies have shown that chronic use of aspirin can enhance expression of several proteins that can potentially affect cardiovascular outcomes. 7,8 In particular, it has been demonstrated that aspirin modulates miRNAs 9,10 and gene expression, such as the nuclear receptor PPARα modulation resulting in an increase in platelet MRP4. 11 Importantly, increased expression of MRP4 in platelets contributes to HARPR.…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin (50 μ mol/L) therapy in human megakaryocytes reduced miR-21 and upregulated MRP4. miR-21 inhibited MRP4 and PPAR α transcription, and aspirin prevented these events [ 74 ].…”
Section: Effects Of Aspirin On Ncrnas In Different Conditionsmentioning
confidence: 99%